Langevin equations for the run-and-tumble of swimming bacteria. Issue 19 (8th May 2018) - Fier, G.; Hansmann, D.; Buceta, R. C.
Abstract : The run and tumble motions of a swimming bacterium are well characterized by two stochastic variables: the speed v ( t ) and the change of direction or deflection x ( t ) = cos  φ ( t ), where φ ( t ) is the turning angle at time t . Abstract : The run and tumble motions of a swimming bacterium are well characterized by two stochastic variables: the speed v ( t ) and the change of direction or deflection x ( t ) = cos  φ ( t ), where φ ( t ) is the turning angle at time t . Recently, we have introduced [G. Fier, D. Hansmann and R. C. Buceta, A stochastic model for directional changes of swimming bacteria, Soft Matter, 2017, 13, 3385–3394.] a single stochastic model for the deflection x ( t ) of an E. coli bacterium performing both types of movement in isotropic media without taxis, based on available experimental data. In this work we introduce Langevin equations for the variables ( v, x ), which for particular values of a control parameter β correspond to run and tumble motions, respectively. These Langevin equations have analytical solutions, which make it possible to calculate the statistical properties of both movements in detail. Assuming that the stochastic processes x and v are not independent during the tumble, we show that there are small displacements of the center of mass along the normal direction to the axis of the bacterial body, a consequence of the flagellar unbundling during the run-to-tumble transition. Regarding the tumble we show, by means of the directional correlation, that the process is not stationary for tumble-times of the order of experimentally measured characteristic tumble-time. The mean square displacement is studied in detail for both movements even in the non-stationary regime. We determine the diffusion and ballistic coefficients for tumble- and run-times, establishing their properties and relationships.